Pengelolaan dan mitigasi dampak limbah masker di Kecamatan Rungkut, Surabaya - Ramadani, Tarikh Azis; Kurniawati, An’nisa; Nindyapuspa, Ayu (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2025)
The utilization of masks will exert an influence on the amount of waste generated. The daily utilization of masks by Indonesians amounts to 159,214,791, contributing to a daily waste generation of 420.03 tons. The generation of mask waste necessitates effective management to ensure optimal balance. In the absence of proper management, mask waste has the potential to exert deleterious effects on the environment. The objective of this study is to ascertain the quantity, dissemination, and selection of the most efficacious management method for mask waste. The study involved the administration of questionnaires, employing a stratified random sampling method to assess the knowledge, management, and distribution of mask waste. The objective of this assessment was to formulate a suitable mask waste management method. The present study demonstrates a correlation between the variables of age, occupation, and education level on knowledge management and the distribution of mask waste. The p-value results for all variables were obtained and are less than 0.05. The methods formulated to manage mask waste generation are the democratization of information on mask waste management, and the implementation of special bins and color-coded bags or bins.